المتشابه اللفظي في القرآن الكريم عند فاضل السامرّائي - عائشة خلف; فتيحة لمّادي (University of El-oued, 2025)
تهدف هذه الدراسة إلى محاولة إبراز جهود أحد علماء اللغة العربية المعاصرين "السامرّائي" في توجيه المتشابه اللفظي بأنواعه التي تناولها في كتبه، ومعرفة منهجه الذي اتّبعه، وبيان مدى علاقة المتشابه بمختلف العلوم:السياق، اللغة، والقراءات، وأسبابالنزول، والاستشهاد بالشعر العربي،خصوصيات الاستعمال القرآني.وقد وجدنا أنّ السامرّائي ركّز على السّياق في إقامة المعنى عند تفسيره لاختيارات الاستعمال القرآني،كما أنّه اتّخذ من علوم اللغة من نحو وصرف ومعجم وبلاغة مطيّة للسّياق في التّفسير. أمّا المنهج الذي اتبعه فقد كان مقلّدا لمن سبقه من علماء التّفسير حين وافقهم في كثير من تقسيماتهم للمتشابه وتوجيهاتهم التي خصّصوا لها كتبا وقد توسع في بعض منها، كما أنّه كان مجدّدا حين خالفهم فأضاف أنواعا جديدة وتوجيهات أخرى لم يفرد لها كتابا خاصّا بل كانت مبثوثة بين طيّات كثير من كتبه الخاصة بالدراسات اللغوية،أو تلك التي اهتمت بالدراسات القرآنية نذكر منها:معاني النحو، الجملة العربية والمعنى، وبلاغة الكلمة، والتعبير القرآني.وأمّا أسلوبه فقد تميّز بالمباشرة والبساطة في اللغة حيث استطاع به استقطاب جمهور كبير لتوجيهاته وتفسيراته البيانية، وفتح بذلك نطاقا أوسع أمام فئات مختلفة من المتتبّعين لسلسلة حلقاته لمسات بيانيّة، بعد أن كان الاهتمام بهذا الموضوع محصورا في فئات خاصّة. ⦁ Abstract : The current study attempts to highlight the efforts made by one of the Arab temporary linguists Sammarra'i in directing the different types of linguistic verbal similarity with which he dealt in his books and writings.We also aimed at identifying the method he followed,and we tried to clarify the extent of relation between verbal similarity and different sciences: context, language and readings, the revelation reasons, quotations from Arab poetry, specificities of Qura'nic use… We found that Sammarra'i focused on contexts to build the meaning when he explained the choices of Qura'nic uses .He also utilized language sciences such as: grammar, lexicon, and rhetoric to explain context. As for the method, Sammarra'i imitated his formers as he approved many of their classifications of verbal similarity as well as their directions to which he dedicated books, however he went further and disagreed with them by adding new types and other directions which were sporadic in many of his books which focused onQura'nic studies such as:Meanings of Grammar ,Arabic Sentence and many Rhetoric of Word , Qura'nic Expression… Sammarra'i 's style was so direct and simple that it attracted a large audience to his Rhetorical explanations and directions.Therefore , he opened a larger range for different categories of followers of his serials "Illustrative Touches" which was formerly restricted to a specific category of audience.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: المتشابه اللفظي، السامرائي، التفسير البياني، السياق،علوم اللغة; Verbal similarity; Sammarra'i; Rhetorical interpretation; Context; Language sciences.